Physician Mediation Theory and Pediatric Media Guidance in the Digital Age: A Survey of Autism Medical and Clinical Professionals. Issue 8 (2nd July 2020) - Mello, Susan; Alper, Meryl; Allen, Anna A.
ABSTRACT: Research on physician mediation suggests that physicians actively discuss media use (e.g., seeking online health information) with their patients. This theory has been limited though with respect to incorporating key behavioral determinants, varied forms of mediation, and samples beyond primary care physicians (MDs). A survey of 335 U.S.-based medical and clinical professionals (MCPs) treating pediatric clients on the autism spectrum (e.g., pediatricians, speech-language pathologists) examined how they advise caregivers about managing their child's recreational media and technology use, also known as media guidance. Results indicate the frequency of these discussions varies by MCP type. Hierarchical regression analyses show, as hypothesized, that additional behavioral and contextual determinants not previously considered (i.e., perceived norms, self-efficacy, information sources and child factors) are significantly associated with positive, negative and redirective mediation practices. Results expand existing theory and justify extending physician mediation research beyond MDs. Implications for clinical practice and health communication research are discussed.